Odwołania do utworów Adama Mickiewicza w wypowiedziach Jana Pawła II wygłoszonych w latach 1978-2005. W kręgu zagadnień międzytekstowych = References to Adam Mickiewicz?s works in the pronouncements of John Paul II enunciated in the years 1978-2005. Around intertextuality issues - Seul, Anastazja (1961- ) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The authoress of the study presents Jonh Paul II's references to characters and output of a romantic poet contained in the pope's statements spoken during his entire pontificate: 1978-2005. The pope uses all literary genres, alludes also to non-literary writings but the most frequently cited seems to be epic: "Sir Thaddeus" ["Pan Tadeusz"] (16 times), "The books of the Polish nation and its pilgrimages" ["Księgi narodu i pielgrzymstwa polskiego"] (6 times), "The rules" ["Skład zasad"] (2 times), "Forefathers' Eve" ["Dziady"], part III (2 times), "Romanticism" ["Romantyczność"] (once), "Ode to youth" ["Oda do młodości"] (once), "Evening talk" ["Rozmowa wieczorna"] (once), "Christmas" ["Boże Narodzenie"] (in: "Sentences and notes" ["Zdania i uwagi?"]) (once).
Keywords: Mickiewicz, Adam (1798-1855); Jan Paweł II, papież (1929-2005); miejsce teologiczne ("locus theologicus"); dialog z kulturą; intertekstualność; dialogue with culture; intertextuality